The effect of home-based stroke rehabilitation bal-ex stroke on activity of daily living and quality of life among patient with ischaemic stroke at rehabilition unit, Hospital Universiti Sains Malaysia - Zainuddin, Nurzaitil Aswani (2015)
Introduction: Stroke is the second commonest cause of death and a leading cause of adult disability worldwide. Reduced stroke mortality leads to increasing need for rehabilitation services to address the disability in stroke survivors. Home-based stroke rehabilitation is an alternative to inpatient rehabilitation to help stroke survivor improve their function and have better quality of life. Objectives: To evaluate the effect of an intervention using video module Bal-ex stroke for home rehabilitation among ischemic stroke patients. Methods: This is a randomized controlled trial (RCT) involving 80 patients with recent mild to moderate ischemic stroke. They were randomly divided into control group and intervention group (40 patients in each group). The intervention group received a combination of home rehabilitation guided by Bal-ex stroke module and twice weekly outpatient follow-up at rehabilitation unit, Hospital USM for 4 months. The control group received only weekly outpatient therapy sessions. Both groups were assessed with Barthel Index for activity of daily living and SSQOL for quality of life at baseline, end of month 2 and end of month 4. Results: At baseline, there was no significant difference in mean ADL and QOL score between control and intervention group. At month 2 and 4, patients in intervention group had significantly higher ADL and QOL score compared to patients in control group (p<0.001). Both groups showed significant improvement in ADL at month 2 (intervention group; p<0.001, control group; p<0.001) and month 4 (intervention group; p<0.001 , control group; p<0.001). Similar changes were observed for QOL at month 2 (intervention group; p<0.001, control group; p<0.001) and month 4 (intervention group; p<0.001, control group; p<0.001). Conclusion: Early home rehabilitation program by using Bal-ex stroke module after ischemic stroke leads to more rapid improvement in function, daily activities and increased quality of life than usual care.